Endobronchial Tuberculosis: Diagnosis and Treatment Approach - Yunita Arliny; Diennisa Shafira Mursalin (Indonesian Society of Respirology (ISR), 2021)
Endobronchial tuberculosis (EBTB) is defined as tuberculosis (TB)infection of the tracheobronchial tract. Tracheal and bronchial involvement from TB infection was first reported by Morten in 1698. Endobronchial tuberculosis is a form of TB that is difficult to diagnose because the lesions are frequently undetectable by sputum examination and chest X-ray alone. Endobronchial tuberculosis is present in 10-40% of active TB patients and more than 90% of cases are accompanied by bronchial stenosis of various degrees. The main goal of therapy in active EBTB is to eradicate Mycobacterium tuberculosis in the tracheobronchial tract and further prevent stenosis. Complications of EBTB apart from airway stenosis are atelectasis, haemoptysis and shortness of breath accompanied by wheezing even after administration of anti-tuberculosis drugs (ATD).